Decoupling Economic Growth and Energy Use. An Empirical Cross-Country Analysis for 10 Manufacturing Sectors - Peter Mulder; Henri L.F. de Groot (Tinbergen Institute, 2004)
This paper provides an empirical analysis of decoupling economic growth and energy use and its various determinants by exploring trends in energy- and labour productivity across 10 manufacturing sectors and 14 OECD countries for the period 1970-1997. We explicitly aim to trace back aggregate developments in the manufacturing sector to developments at the level of individual subsectors. A cross-country decomposition analysis reveals that in some countries structural changes contributed considerably to aggregate manufacturing energy-productivity growth and, hence, to decoupling, while in other countries they partly offset energy-efficiency improvements. In contrast, structural changes only play a minor role in explaining aggregate manufacturing labour-productivity developments. Furthermore, we find labour-productivity growth to be higher on average than energy-productivity growth. Over time, this bias towards labour-productivity growth is increasing in the aggregate manufacturing sector, while it is decreasing in most manufacturing subsectors.
Keywords: O13; O47; O5; Q43; 330; energy productivity; labour productivity; convergence; sectoral analysis; Wirtschaftswachstum; Energiekonsum; Arbeitsproduktivität; OECD-Staaten